Collegiate and professional ice hockey athletic trainers` hydration practices and knowledge: Part 1 - Emerson, D. M.; Torres-McGehee, T. M.; Yeargin, S. W.; Dolan, K.; deWeber, K. K. (International Journal of Athletic Therapy & Training, 2020)
Despite cool environments, ice hockey athletes are predisposed to hypohydration due to extensive equipment, high intensity activity, and high sweat rates. The purpose of this study was to determine hydration practices and awareness of fluid recommendations among athletic trainers (ATs) working with NCAA Division I, NCAA Division III, and professional ice hockey teams. Most professional ATs (90.1%) utilized at least one hydration status measure, while 61.7% of collegiate ATs did not measure hydration. Compared to Division I, more Division III ATs did not have electrolyte supplements (p < .001) and believed they did not have adequate access through budget/sponsorship (p < .001). Both professional (72.0%) and collegiate (53%) ATs reported athletes had open access to electrolyte supplements or gave them to any athlete who asked. Athletic trainers provided patient education and had fluids accessible to athletes. Areas to improve clinical practice include monitoring electrolyte supplement access and collegiate ATs assessing hydration status.